Pengaruh Kompetensi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Bidang Pengawasan Dan Pengendalian Kantor Dinas Tata Ruang Dan Bangunan Kabupaten Tangerang - Suhartono; Sudahlan, Dahlan (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2023)
The aim of this research is to determine and analyze the influence of competency and work environment on employee performance in the field of supervision and control at the Tangerang Regency Spatial Planning Service Office (DTRB). The number of samples in this research was 55 people. The data collection technique uses a Likert scale, while the data analysis technique uses multiple linear regression analysis. The results of this research reveal that competency (X1) influences employee performance (Y). This can be proven by the results of the hypothesis test value tcount > ttable or (3.423 > 0.266). The work environment (X2) has a positive and significant effect on employee performance (Y). This can be proven by the results of the hypothesis test value tcount > ttable or (3.307 > 0.266). Competency (X1) and Work Environment (X2), have a positive effect simultaneously. This can be proven by the results of the hypothesis test value tcount > ttable or (17.756 > 3.172). Thus, it can be said that the competency and work environment variables simultaneously have a significant effect on the Employee Performance variable.